An Investigation to Replace sand with Kunkur Quarry dust as fine Aggregates in Concrete. - Mumo Ndolo, Dennis; Abednego, Gwaya; Diang’a, Stephen (International Journal of Soft Computing and Engineering (IJSCE), 2020)
Following a national outcry by environment management organizations both governmental and non-governmental to preserve rivers it’s seen to be strongly backed by political leaders which is posing a great threat to the future of construction industry. This therefore calls for thorough investigations on alternative materials which can potentially be used to replace sand either partially or fully to help preserve rivers which are the major source of sand. Sand harvesting is associated with drying up of rivers which causes water problems to the communities during the dry period. At present, the identified alternative sources are manufactured sand (mechanically crushed rock sand).This source proves to be expensive as machinery must be purchased purposely for crushing the aggregates and extra cost must be incorporated with this process. The alternative sought should therefore be of a lower cost compared to what is currently in use. The research examined the use of Kunkur fines to test its potential for use as an alternative to preserve the drying rivers. The research used quantitative design to examine its variables which extend from the raw materials, fresh and the hardened concrete. Kunkur fines from EAPCC quarry is a potential material for partially replacing sand up to 50% for fine aggregates in concrete as it qualifies the tests which are required to regard a material as having sufficient structural strength and suitable for use as fine aggregate. An increase of Kunkur fines in the blend slightly reduces the strength of concrete. Up to 50% replacement the blend gives sufficient structural strength of 20N/mm2 and above with further increase of Kunkur recording lower values than the design strength. Kunkur has low silt content which is slightly higher than that of sand by 0.91% but below the maximum required percentage by BS 812 of 5%. The research recommends the use of Kunkur fines as it will help reduce the amount of sand harvested in the rivers annually by half and this will reduce the effect of water scarcity in the affected areas. Its use will also solve the problem of heap disposal by the EAPCC in the mines as the waste will be appropriately used in the construction industry.
Keywords: Sand; Kunkur Quarry dust; Aggregates; Concrete